Thermostable α-Glucan Phosphorylase-catalyzed Enzymatic Chain-elongation to Produce 6-Deoxygenated α(1→4)-Oligoglucans - Kadokawa, Jun-ichi; Lee, Le H.; Yamamoto, Kazuya (Current Organic Chemistry, 2021)
Herein, the synthesis of 6-deoxygenated α(1→4)-oligoglucans via thermostable α- glucan phosphorylase (from Aquifex aeolicus VF5)-catalyzed enzymatic chain-elongation is reported from a maltotriose primer using a non-native substrate, 6-deoxy-α-D-glucose 1- phosphate. The enzymatic reaction of the two substrates mainly produced a tetrasaccharide with one 6-deoxy-α-D-glucose unit at the non-reducing end, together with a minor pentasaccharide with two 6-deoxy-α-D-glucose units. The enzymatic chain-elongation from the primer in the presence of 6-deoxy-α-D-glucose 1-phosphate and a native substrate, α-D-glucose 1- phosphate, afforded 6-deoxygenated α(1→4)-oligoglucans with varying degrees of polymerization. This enzymatic chain-elongation catalyzed by thermostable α-glucan phosphorylase is an efficient method to produce non-natural oligosaccharides, that is, 6-deoxygenated α(1→4)- oligoglucans.
Keywords: maltooligosaccharide primer